Live in your head : When attitudes become form : works - concepts - processes - situations - information - Burton, Scott; Müller, Grégoire; Szeemann, Harald; Trini, Tommaso; Kunsthalle Bern, Bern (Bern : Kunsthalle Bern, 1969)
Andre, Carl ; Anselmo, Giovanni ; Artschwager, Richard ; Bang, Thomas ; Bark, Jared ; Barry, Robert ; Beuys, Joseph ; Bochner, Mel ; Boetti, Alighiero ; Boezem, Marinus ; Bollinger, Bill ; Buthe, Michael ; Calzolari, Pierpaolo ; Cotton, Paul ; Darboven, Hanne ; Dibbets, Jan ; van Elk, Ger ; Ferrer, Rafael ; Flanagan, Barry ; Glass, Ted ; Haacke, Hans ; Heizer, Michael ; Hesse, Eva ; Huebler, Douglas ; Icaro, Paolo ; Jacquet, Alain ; Jenney, Neil ; Kaltenbach, Stephen ; Kaplan, Jo Ann ; Kienholz, Edward ; Klein, Yves ; Kosuth, Joseph ; Kounellis, Jannis ; Kuehn, Gary ; LeWitt, Sol ; Lohaus, Bernd ; Long, Richard ; Louw, Roelof ; de Maria, Walter ; McLean, Bruce ; Medalla, David ; Merz, Mario ; Morris, Robert ; Nauman, Bruce ; Oldenburg, Claes ; Oppenheim, Dennis ; Panamarenko ; Pascali, Pino ; Pechter, Paul ; Pistoletto, Michelangelo ; Prini, Emilio ; Raetz, Markus ; Ruppersberg, Allen ; Ruthenbeck, Reiner ; Ryman, Robert ; Sandback, Frederick Lane ; Saret, Alan ; Sarkis ; Schnyder, Jean-Frederic ; Serra, Richard ; Smithson, Robert ; Sonnier, Keith ; Tuttle, Richard ; Viner, Frank Lincoln ; Walther, Franz Erhard ; Wegman, William ; Weiner, Lawrence ; Wiley, William T.
alg. bibliog. [1 p.]
biog., ind. tent., gr. tent., bibliog. per kunstenaar [1 p.]
Duits
Engels
Frans
Italiaans